Architecture, Film, and the In-between (Intellect, 2026)
The long-established dialogue between architecture and film offers an interdisciplinary platform for a critical examination of spaces of in-between. Apart from architecture informing scenography and cities serving as backdrops to the moving image, films have actively participated in shaping the public opinion about architecture and its allied disciplines. While architecture and design may not necessarily be central themes in a film, their spatial contextualization of the narrative informs cinematic productions. Screen, Space, and the In-Between looks at both the filmic imagination/representation of architectural in-betweenness, as well as the in-between spaces within the inherent architectural structure of filmic expression. On the one hand, cinematic production serves as a site to project utopian fantasies of the built environment, and on the other hand, the processes, tools, and methods involved in both architecture and film, function as mediators between abstract ideation and its materialized manifestation. The book interrogates the filmic creation of spatial imaginaries through the anthropological lens, especially as the disciplines in the built environment react to the liminal spaces of the cinematic. It adopts cinematic experiences of the built environment as a vantage point to reframe ongoing theoretical debates about liminal spaces. Foreword by Mark Foster Gage Contributors: Giuliana Bruno, Beatriz Colomina, James F. Kerestes, Graham Harman, Ferda Kolatan, Juhani Pallasmaa, Eva Perez De Vega, Mehmet Sahinler, Patrik Schumacher, Maria Sieira, Alican Taylan, Vahid Vahdat, Jason Vigneri-Beane, Jon Yoder, Michael Young